Perfectionism in adolescents with eating disorders (European Journal of Health Research, 2020)
Perfectionism has been considered a significant risk factor for psychopathology and a typical personality characteristic in people suffering from eating disorders (ED). This study aims to know the relationship between perfectionism and depressive symptomatology, self-esteem and body dissatisfaction in adolescents diagnosed with ED. The sample was composed by 100 adolescents (M age = 14.91, SD = 1.094) diagnosed with ED who went outpatiently to a specific child-juvenile ED unit of the National Health System. All patients completed the perfectionism scale of the Inventory of Eating Disorders (EDI-3), the Spanish Child Depression Questionnaire (CEDI-II), the Rosenberg Self-Esteem Scale (RSES), and the Body Form Questionnaire (BSQ-34). Results indicate that the perfectionism scale of EDI-3 correlates significantly positively with CEDI-II (r =, 336, p =, 001) and BSQ-34 (r =, 199, p =, 45), and in a negative way with the RSES (r = -, 337, p =, 001). Adolescents diagnosed with ED who score higher on perfectionism show greater depressive symptoms and body dissatisfaction, and lower self-esteem. We believe that emphasizing the treatment of perfectionism could result in a psychopathological improvement of these patients.